Kontribusi dan Trend Produksi Padi Daerah Pengembangan Sulawesi Selatan, Indonesia - Arifin Arifin; Muhammad Arsyad Biba; Azisah Azisah; Mohammad Anwar Sadat; Sri Mardiyati (JURNAL AGRICA, 2022)
Rice is still a strategic commodity in the economy and national food security. Improvement effortsto rice production can be impelemented and one of them is through the intensification of riceplants. The aim of this study was to analyze the contribution and trend of rice production indevelopment areas to rice production in South Sulawesi. This study uses secondary time seriesdata for rice production in South Sulawesi and central areas for a period of 15 years (2004 -2018). For development areas in South Sulawesi, there are 12 regencies : Selayar, Sinjai,Bulukumba, Bantaeng, Jeneponto, Takalar, Gowa, Maros, Pangkep, Barru, Enrekang and Tator. Descriptive and quantitative methods and analyzes were used to determine the contribution andtrend of rice production in development areas to rice production in South Sulawesi. For theanalysis of rice production trends in the development area of South Sulawesi is the least squaremethod. The results of the research on the contribution of development area rice production toSouth Sulawesi rice production for 15 years (2004 - 2018) showed an increase. The trend of riceproduction in the development area of South Sulawesi has increased with the assumption that thecurrent situation is the same as that in the future.